1986
DOI: 10.1093/brain/109.3.537
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Depression and Lesion Location

Abstract: Recent evidence suggests that poststroke depression is associated with the location of the brain infarct, proximity to the frontal pole being associated with greater depression following left hemisphere injury, and an opposite relationship being seen with injury to the right hemisphere. This study was designed to replicate and extend previous investigation of this issue. Depression was assessed following recent stroke in patients with localized right (n = 16) or left (n = 19) hemisphere lesions. No overall dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(91 citation statements)
references
References 0 publications
10
76
0
5
Order By: Relevance
“…In the end, 26 original reports were included in the review (Table). 10, Ten articles observed no significant association between lesion locations and the frequency or severity of PSD. * Two studies cited a significant association between right hemisphere strokes and PSD 33,45 ; 4 studies noted a significant association between left hemisphere strokes and PSD 7,28,30,41 ; 3 studies noted greater depression associated with left hemisphere basal ganglia lesions 31,39,40 ; and 7 studies noted changes in the association between lesion location and PSD over time.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the end, 26 original reports were included in the review (Table). 10, Ten articles observed no significant association between lesion locations and the frequency or severity of PSD. * Two studies cited a significant association between right hemisphere strokes and PSD 33,45 ; 4 studies noted a significant association between left hemisphere strokes and PSD 7,28,30,41 ; 3 studies noted greater depression associated with left hemisphere basal ganglia lesions 31,39,40 ; and 7 studies noted changes in the association between lesion location and PSD over time.…”
Section: Resultsmentioning
confidence: 93%
“…10,32,33,38,47 As shown in Figure 1, the 95% CIs for individual studies were wide, and the test of heterogeneity was highly significant ( 2 ϭ75.45, PϽ0.00001), indicating substantial variation in OR among studies. As noted earlier, much of this variation is believed to reflect the methodological differences of the literature.…”
Section: Bhogal Et Al Lesion Location and Poststroke Depressionmentioning
confidence: 96%
See 1 more Smart Citation
“…(1986) have indicated that the sex differences in the frequency of PSD may be masked by the excluding patients, who had a history of psychiatric disorder. More especially, it is reported that there is a sex‐specific prevalence of PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos não encontraram associação entre a lateralidade do AVC e a ocorrência de depressão em pacientes de centro de reabilitação 37 e da comunidade 38,39 .…”
Section: Depressão Pós-avcunclassified